PRODUKTIVITAS PENGELUARAN DOLOK KAYU TUSAM DENGAN SISTEM KABEL LAYANG IWAFUJI 115 - Zakaria Basari (Jurnal Penelitian Hasil Hutan, 2002)
This report deals with assessing the performance of  tusam (Pinus merkusii Jungh et de Vries)  log - removal using particular skyline system.  The assessment in this regard is pointed out by the aim of this study, i.e.   observing the productivity and operation cost of such removal.Related with those cases, investigation has been conducted and located in Cikajang Sub Forestry District,  Garut Forest District,  under the Indonesian State Forest Enterprise in West Java.  The  topographical location has a slope at about 5° - 50°  with altitude ranging around 900 - 1000 m above sea level.  The skyline machine used was a yarder manufactured in Japan with the brand name as "IWAFUJI" and engine power at115 HP.  The harvesting or removal of tusam  log was done using a clear-cutting system.The result revealed that the removal productivity varied from 25.07  to 43.17  m3  hm per hour with average at 33.33  m3 hm per hour. Meanwhile,  the corresponding production cost was Rp.  16,879.3 per m3.   It turned out that such productivity (Y) was significantly affected by real removal frequency  (X),  which further could be expressed in regression equation Y = 1.0659  + 0.1245 X (r=0.5852)  with F-calc = 4.15 greater than F-table = 2.1).  The opening soil was 5 percent.